Experimental investigation of the plugging mechanisms of non-consolidated prepacked gravel screens. (11th October 2021) - Ma, Chengyun; Feng, Yongcun; Deng, Jingen; Wang, Wei; Li, Shuqian; Chu, Mingming; Gui, Yun
Abstract: Sand production is one of the most common problems in exploiting poorly consolidated sands reservoirs in general. It can cause numerous production obstacles, such as plugging of surface processing equipment, eroding downhole and surface production equipment, sand filling up the wellbore, impairing of well productivity, and so on. Hence, sand control is required for sand production in oil and gas wells. Mechanical sand control screen is the most commonly used method of sand control, but it is easy to be plugged during production, leading to reduced production or even unexpected shutdown of oil wells. Gravel packing sand control method is the most effective sand control method, but the operation risk is high, the cycle is long, and the cost is high. So far, no suitable sand control method has been found. In this study, a non-consolidated prepacked gravel screen (NCPPGS) was introduced to replace the gravel packing sand control method for reducing cost and risk of gravel packing sand control method, and effectively preventing plugging of mechanical sand control screen. To achieve the goal, the plugging mechanisms and progress of NCPPGS were systematically studied through a series of experiments. A new sand retention testing (SRT) method was employed in this study. Impacts of the structural, formation, and production parameters on the plugging of NCPPGS were experimentally investigated. Results show that the anti-plugging ability of the NCPPGS is affected by the packing density and gravel size simultaneously. With increasing pack density, gravel size should be appropriately enlarged to maintain the original flow capacity. Obviously, the sand retaining precision of NCPPGS differs in the gravel packing sand control method. In addition, results present that montmorillonite can cause more serious plugging of screens due to the strong fluid–solid coupling effect compared with illite and kaolinite. Based on the above research results, designing low production rates at the beginning of the production can further help control screen plugging. Highlights: The plugging mechanisms of non-consolidated pre-packed screens are investigated. A new experimental method for sand control is introduced. Influences of screen parameters and formation parameters on plugging are revealed.